Analisis Kemampuan Literasi Matematis Siswa dalam Pemecahan Masalah Matematika pada Siswa Kelas VIII SMPN 8 Mataram - Putra, Clevery Agung Sayuthi; Baidowi; Nilza Humaira Salsabila; Harry Soepriyanto (FKIP Universitas Mataram, 2024)
This study aims to describe the ability of mathematical literacy in solving mathematical problems of students in class VIII F SMPN 8 Mataram on SPLDV material. This research used descriptive qualitative method with purposive sampling technique, involving 33 students. Data were collected through mathematical literacy tests, written tests, and interviews. Based on the research results, 22 students with low mathematical literacy skills with a percentage of 16.67%, 8 students with moderate literacy skills with a percentage of 53.70%, and 3 students with high literacy skills with a percentage of 92.59%. Students with high problem solving have high mathematical literacy skills, this is evidenced by the achievement of students in answering questions by fulfilling all stages or indicators used. Students with moderate problem solving have moderate mathematical literacy skills, where at the formulate stage or understanding the problem and planning problem solving, moderate category students have not been able to formulate information from the problem into mathematical form, while for the employ and interpret stages it is good. Whereas students with low problem solving have low mathematical literacy, this is evidenced by the inability of students to understand and plan problem solving at the formulate stage, it is still difficult to plan solutions with certain methods at the employ stage and at the interpret stage they do not do a back check because they do not know how to solve the problem.